Procedimiento metodológico para la gestión turística del cantón Bolívar en vinculación con la Escuela Superior Politécnica Agropecuaria de Manabí MFL - García García, María Liseth (2016)
This thesis aims to design a methodological procedure for the tourist management in Canton Bolívar with the linkage of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. The research was bibliographical, descriptive and on the field, it was developed in Canton Bolívar, Province of Manabí, in which the ESPAM MFL has a direct incidence. This study is part of an institutional project of the Tourism Career developed in the territory where the improvement of sustainable community tourism management is sought, based on the National Plan for Good Living and the Land Management Plan of the canton. The proposed methodology is the result of the consideration of several authors, and is formed by three phases and nine activities that respond to the objectives established, addressing the local needs and linking the processes of institutional interrelation between ESPAM MFL and the GAD of Canton Bolívar. The diagnosis was characterized by political, environmental, geographic, economic and tourist information of the area under study, through the application of data collection cards. Secondary sources of research made by the Tourism Ministry of Ecuador were used. The needs of communities and tourist entrepreneurs were evaluated through technical visits, interviews, surveys, and also the information needed was obtained from institutional plans. A procedure that contributes to systematize an adequate tourist management was formulated; the political and legal bases of the management as well as a program of monitoring and evaluation were established.